PERBANDINGAN EFEKTIVITAS ANTARA JUS WORTEL DAN AIR KELAPA HIJAU TERHADAP TINGKAT DISMENOREA PADA MAHASISWA ASRAMA PUTRI UNIVERSITAS BATAM - Hajiansyah, Abdelzikri; Astiah, Andi Asda; Isramilda, Isramilda (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2024)
Background: Dysmenorrhea, or menstrual pain, is a common complaint experienced by women during menstruation. Factors such as dietary patterns and consumption of specific beverages can play a role in reducing the severity of dysmenorrhea. One such beverage with the potential to alleviate menstrual pain is carrot juice and green coconut water, both rich in nutrients and anti-inflammatory compounds. Hence, it is crucial to investigate the comparison between carrot juice and green coconut water regarding the severity of dysmenorrhea. Methods: This study utilized a Quasi-Experimental research design with a Non-equivalent approach. The research was conducted at the Female Dormitory of Batam University from November 2023. The sampling technique used was Simple Random Sampling, with a total sample size of 42 or 14 sample in each group. Results: Based on the One-Way ANOVA test, the obtained result indicates that the significance value of the ANOVA test (Sig.) is 0.000 (< 0.05). Therefore, it can be concluded that there is a significant difference between the effects of carrot juice and green coconut water on the reduction of dysmenorrhea levels. Conclusion: Based on the research findings, it can be concluded that the intervention of green coconut water is more effective in reducing menstrual pain compared to the intervention of carrot juice among female dormitory students University of Batam in 2023.